Analysis of SIPD-RI Implementation on Financial Report Quality with Accountability as an Intervening Variable - Satrio, Satrio; Usman, Halim; Ayu Dasila, Rifqa (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to analyze the direct and indirect influence of the implementation of the Regional Government Information System of the Republic of Indonesia (SIPD-RI) on the quality of financial reports, with accountability as an intervening variable, in the Palopo City Regional Government. This research uses a quantitative approach with a survey method applied to 157 respondents who are local government officials involved in financial management and reporting. Data was collected thru questionnaires and analyzed using path analysis to test the causal relationships between the research variables. The research results indicate that the implementation of SIPD-RI directly and significantly affects the quality of financial reports and accountability. Accountability was also proven to significantly influence the quality of financial reports and to mediate the effect of SIPD-RI implementation on the quality of financial reports. This finding confirms the importance of strengthening infrastructure, training, and management commitment in supporting the optimization of SIPD-RI and accountability to improve the quality of regional financial reports. This research contributes to the development of more transparent, accountable, and high-quality local financial governance, and serves as a reference for local governments and subsequent researchers in optimizing the implementation of SIPD-RI